Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte" - Šebo, Jozef (1966)
Reprint. From: portfolio "Revolučný Odkaz Slovenského Národného Povstania v politickom plagáte".